House and garden book of garden decoration - Coats, Peter (New York : The Viking Press, 1970)
This book is about garden decorations. Some of the pictures it contains are of very grand, royal gardens.
Introduction -- Terraces and roof gardens -- Steps, paths, and pergolas -- Summer houses -- Walls, fences and gates -- Water in the garden -- Art in the garden -- Colour and form.
Keywords: HOUSE GARDEN -- ROYAL GARDEN